To expand the expression \((-4x - 3)(3x^2 - x - 1)\), we'll use the distributive property (also known as the FOIL method for binomials).
-
First, distribute \(-4x\) to each term in the second polynomial \((3x^2 - x - 1)\):
\[ -4x \cdot 3x^2 = -12x^3 \] \[ -4x \cdot (-x) = 4x^2 \] \[ -4x \cdot (-1) = 4x \]
So, combining these yields: \[ -12x^3 + 4x^2 + 4x \]
-
Next, distribute \(-3\) to each term in the polynomial:
\[ -3 \cdot 3x^2 = -9x^2 \] \[ -3 \cdot (-x) = 3x \] \[ -3 \cdot (-1) = 3 \]
Combining these gives: \[ -9x^2 + 3x + 3 \]
-
Now, we combine all these results together:
\[ -12x^3 + 4x^2 + 4x - 9x^2 + 3x + 3 \]
-
Combine like terms:
\[ -12x^3 + (4x^2 - 9x^2) + (4x + 3x) + 3 \] \[ -12x^3 - 5x^2 + 7x + 3 \]
The expression \((-4x - 3)(3x^2 - x - 1)\) in standard form is:
\[ \boxed{-12x^3 - 5x^2 + 7x + 3} \]